Exploring liquid-solid interface based triboelectrification, structures, and applications - Kaja, Kushal Ruthvik; Hajra, Sugato; Panda, Swati; Belal, Mohamed A.; Pharino, Utchawadee; Khanbareh, Hamideh; Vittayakorn, Naratip; Vivekananthan, Venkateswaran; Bowen, Chris; Kim, Hoe Joon (My University, 2024)
In recent years, there has been a quest to accelerate the search for efficient and sustainable energy harvesting technologies due to challenges from fossil fuel depletion and environmental concerns. There is also a continous demand for autonomous sensing in our growing connected world. The liquid-solid triboelectric nanogenerator (L-S TENG) has emerged as a viable alternative, notably for generating mechanical energy from water. Despite extensive study into liquid-solid contact electrification techniques, a significant need remains to improve energy harvesting efficiency in L-S TENG systems. This comprehensive analysis delves into recent advances in energy harvesting from water, with a particular emphasis on understanding the interaction dynamics between liquid-solid interfaces when using triboelectric nanogenerators for energy conversion. This review summarizes recent developments in the structural design and applications of liquid-solid triboelectrification, focusing on improving TENG output performance. In addition, new insights are provided on the potential impact and future technical hurdles facing L-S TENG technologies. By offering new insights into current knowledge and future research directions, this review aims to guide progress in the field of L-S TENG energy harvesting.
Keywords: Liquid-Solid; Nanogenerator; Self-powered; Water droplets